2018
DOI: 10.1111/evj.13046
|View full text |Cite
|
Sign up to set email alerts
|

Equus caballus papillomavirus 8 (EcPV8) associated with multiple viral plaques, viral papillomas, and squamous cell carcinoma in a horse

Abstract: Summary Background Equus caballus papillomavirus 8, a recently discovered virus, has been reported to cause generalised papillomavirus in horses. Objectives To describe a case in which multiple viral plaques, viral papillomas, squamous cell carcinoma (SCC) in situ and invasive squamous cell carcinoma (ISCC) were associated with EcPV8 in a horse. Study design Case report. Methods A 16‐year‐old mixed breed horse presented with dozens of raised crusted papular to nodular lesions over a course of 4 years. Masses h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Since there are other papillomaviruses described to be associated with equine genital lesions, and co-infections with other PVs were reported [32][33][34], also broad-range PV PCR using CP4/5 [35] and Fap 59/64 [36] primer sets was done to detect other potentially involved PVs. These primers are designed to also detect the equine PVs type 3-8 [32][33][34]37] and the sarcoid associated bovine PVs type 1 and 2 [38]. Using these two broad-range PV primer sets, no other PVs were detectable, hence it is not likely that other PVs were involved in the development of the lesions assessed in this study.…”
Section: Aetiological Association Of Ecpv2 With Equine Penile Sccs Anmentioning
confidence: 99%
“…Since there are other papillomaviruses described to be associated with equine genital lesions, and co-infections with other PVs were reported [32][33][34], also broad-range PV PCR using CP4/5 [35] and Fap 59/64 [36] primer sets was done to detect other potentially involved PVs. These primers are designed to also detect the equine PVs type 3-8 [32][33][34]37] and the sarcoid associated bovine PVs type 1 and 2 [38]. Using these two broad-range PV primer sets, no other PVs were detectable, hence it is not likely that other PVs were involved in the development of the lesions assessed in this study.…”
Section: Aetiological Association Of Ecpv2 With Equine Penile Sccs Anmentioning
confidence: 99%
“…Two of the PCRs used degenerate primers for conserved regions to screen for a broad spectrum of PV types with the FAP59/FAP64 assay targeting the L1 gene and the CP4/CP5 assay targeting the E1 gene with HPV6 plasmid DNA as the positive control. 2,12 Nine published EcPV-specific PCRs were used to screen for the DNA of EcPVs 2-7 in the samples, following the published protocols (Table 1). 2,[10][11][12] .…”
Section: Pcrmentioning
confidence: 99%
“…2,12 Nine published EcPV-specific PCRs were used to screen for the DNA of EcPVs 2-7 in the samples, following the published protocols (Table 1). 2,[10][11][12] . The EcPV-specific PCRs ran without positive controls.…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…As anticipated on the basis of previous reports reviewed by Sykora et al [4] all lesions tested positive for EcPV2 DNA as revealed by virus type-specific PCR. Since there are other papillomaviruses described to be associated with equine genital lesions, and co-infections with other PVs were reported [32][33][34], also broad-range PV PCR using CP4/5 [35] and Fap 59/64 [36] primer sets was done to detect other potentially involved PVs. These primers are designed to also detect the equine PVs type 3-8 [32][33][34]37] and the sarcoid associated bovine PVs type 1 and 2 [38].…”
Section: Aetiological Association Of Ecpv2 With Equine Penile Sccs Anmentioning
confidence: 99%